Perspectives on casein interactions. (October 2018) - Lucey, John A.; Horne, David S.
Abstract: Over the past 60 years considerable progress has been made on understanding the nature of casein interactions. Although there is ongoing debate, most researchers now view that casein micelles are assembled due to the concerted action of two major types of interactions, namely hydrophobic interactions, and formation of calcium phosphate nanoclusters across phosphoserine clusters. This paper provides the authors' perspectives on these interactions, reviews evidence supporting the involvement of these two types of interactions, critiques some of the proposed models, and gives several examples where these interactions are manipulated to modify the functionality of dairy products.